Practical Measures for Dealing With the Struggles of Nurses Caring for People With Amyotrophic Lateral Sclerosis Comorbid With Cognitive Impairment in Japan - Ushikubo, Mitsuko; Nashiki, Emiko; Ohtani, Tadahiro; Kawabata, Hiromi (Frontiers in Psychology, 2021)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease for which there is currently no cure. This study aimed to explore the situations with which nurses struggled, their implemented practical measures, and the challenges they experienced when caring for patients with ALS comorbid with cognitive impairment (hereinafter, targeted patients). In this qualitative study, we conducted a survey with nurses (n=121) experienced in caring for ALS patients; the survey contained a free-writing section in which participants described their struggles regarding care delivery for these patients. To collect data on practical measures that nurses had already implemented or wanted to propose regarding care delivery for the targeted patients, we conducted four focus group interviews (n=22). We used a qualitative inductive approach to extract the categories. Fifty-eight nurses (49.6%) completed the free-writing survey section. The situations in which nurses struggled in care for the targeted patients were organized into three categories: “Patients’ strong persistency on specific requirements for nursing assistance in their daily lives,” “Patients’ problematic behaviors toward nurses,” and “Struggles in communicating with and understanding patients’ wishes.” Nurses reported these situations as stressful, and they affected care quality. The practical measures implemented when caring for the targeted patients were organized into five categories: “Cognitive impairment assessment,” “Care delivery to deal with patients’ strong persistency on specific requirements for assistance in their daily lives,” “Communication,” “Supporting the decision-making process,” and “Collaboration between the hospital and the community.” Multidisciplinary collaboration in the hospital, and collaboration between the hospital and the community from an early stage is necessary to share the results of the assessment and diagnosis of cognitive impairment. Our evidence underlines that guideline and care manual establishment may lead to improved care delivery and to the unification of care deliveries to respond to patients’ strong persistency.